Variation in Biliary Complication Rates Following Liver Transplantation: Implications for Cost and Outcome. Issue 1 (January 2015) - Axelrod, D. A.; Dzebisashvili, N.; Lentine, K. L.; Xiao, H.; Schnitzler, M.; Tuttle‐Newhall, J. E.; Segev, D. L.
Abstract Although biliary complications (BCs) have a significant impact on the outcome of liver transplantation (LT), variation in BC rates among transplant centers has not been previously analyzed. BC rate, LT outcome and spending were assessed using linked Scientific Registry of Transplant Recipients and Medicare claims (n = 16 286 LTs). Transplant centers were assigned to BC quartiles based upon risk‐adjusted observed to expected (O:E) ratio of BC separately for donation after brain death (DBD) and donation after cardiac death (DCD) donors. The median incidence of BC was 300% greater in the highest versus lowest DBD quartiles (19.0% vs. 5.9%) and varied 250% between DCD quartiles (20.3%–8.4%). Donor and recipient characteristics suggest that high BC centers actually used lower donor risk index organs, fewer split livers and fewer imports (p < 0.001 for all). Transplant at a center in the highest O:E quartile was associated with increased posttransplant mortality (adjusted hazard ratio [aHR] 2.53, p = 0.007) in DCD transplant and increased graft loss (aHR 1.21, p = 0.02) in DBD transplant. Medicare spending was $22 895 (p < 0.0001) higher at centers in highest versus lowest BC quartile. In summary, BC rates vary widely among transplant centers and higher rates are a marker for an increased risk of death, graft failure and health‐care spending.